37 Factors Influencing Mealtime Care for People with Dementia Living in Care Homes: An Ethnographic Study. (16th March 2021) - Faraday, J; Abley, C; Exley, C; Patterson, J
Abstract: Introduction: More and more people with dementia are living in care homes. Often they depend on care home staff for help with eating and drinking. It is essential that care home staff are able to provide good care at mealtimes. This study used ethnography to identify factors influencing mealtime care for this population. Methods: Over twenty-five hours of mealtime observations were conducted in two UK care homes with diverse characteristics. Observations focused on interactions between care home staff and residents living with dementia. Twenty-two semi-structured interviews were carried out with care home staff, family carers, and visiting health and social care professionals, to explore mealtime care from their perspectives. The study used a constant comparison approach, so that data from early observations and interviews were explored in more depth subsequently. Results: Five factors were identified which influenced mealtime care for people with dementia living in care homes. These were: environment (such as background music and building layout); kitchen and food (including connectivity between kitchen staff and others); staffing (for example: staff ratios and allocation); knowledge and support (including training, resources and supportive culture); and relationship with wider care team (such as family involvement, and the role of visiting health and social care professionals). Conclusions: This study is part of a bigger project which will develop a staff training intervention to improve mealtime care for people with dementia living in care homes. The intervention will be informed by these findings, and by complementary evidence on good practice in mealtime care (from primary and secondary studies). It is anticipated that good mealtime care may improve quality of life for care home residents, and reduce hospital admissions.